Investigating market power in the German dairy industry - Jasmin Wehner; Jan-Henning Feil; Xiaohua Yu (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Market power in economic theory is defined as deviations from marginal cost pricing, which results in unfair competition and welfare losses. In complex agri-food supply chains, the exercise of market power is a significant contributor to welfare losses, as multiple actors throughout the chain can exert such power. However, the potential dual role of dairy processors-as both buyers in the raw milk market and sellers in the output market-has received little attention so far. Using a panel data set with 323 observations from major German dairy processors between the years 2010 and 2021, we show that dairy processors exercise both, oligopsonistic as well as oligopolistic market power. Results suggest that dairy processors take advantage of their central position in the dairy supply chain, and buy milk from dairy farmers 9.2 percent below the value of the marginal product and sell processed milk to retailers 1.1 percent above the marginal costs. We demonstrate that it is important to incorporate the dual role of supply chain actors in market power analyses. In order to reduce welfare losses generated by market power, we recommend that the federal cartel authority should monitor market actors within the dairy supply chain continuously and consider the dual role of market actors in their reports and recommendations to the government.
Keywords: Q12; Q13; L13; 330; Market power; Nonparametric and Solow residual-based tests; Dairy supply chain